Approach of minimal invasive monitoring and initial treatment of the septic patient in emergency medicine (2018)
Sepsis and septic shock constitute a complex disease condition that requires the engagement of several medical specialties. A great number of patients with this disease are constantly admitted to the emergency department, which warrants the need for emergency physicians to lead in the recognition and early management of septic patients. Timely and appropriate interventions may help reduce mortality in a disease with an unacceptably high mortality rate. Poor control of cellular hypoperfusion is one of the most influential mechanisms contributing to the high mortality rate in these patients. This article aims to make an evidence-based approach and an algorithm for the active identification of hypoperfusion in patients with suspicion of severe infection, based on both clinical variables (capillary refill, mottling index, left ventricular function by ultrasound, temperature gradient, etc.) and laboratory-measured variables (lactate, central venous oxygen saturation [ScvO2], and venous-to-arterial carbon dioxide tension difference [P (v?a) CO2]). Such variables are feasible to use in the emergency department and would help to explain the cause behind the inadequate oxygen use by cells, thereby guiding treatment at the macrovascular, microvascular, or cellular level. © 2018 Devia Jaramillo et al.